2002
DOI: 10.1002/ijc.10200
|View full text |Cite
|
Sign up to set email alerts
|

Oral cancer in southern India: The influence of smoking, drinking, paan‐chewing and oral hygiene

Abstract: Between 1996 and 1999 we carried out a case-control study in 3 areas in Southern India (Bangalore, Madras and Trivandrum) including 591 incident cases of cancer of the oral cavity (282 women) and 582 hospital controls (290 women), frequency-matched with cases by age and gender. Odds ratios (ORs) and 95% confidence intervals (CIs) were obtained from unconditional multiple logistic regressions and adjusted for age, gender, center, education, chewing habit and (men only) smoking and drinking habits. Key words: o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
253
1
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(287 citation statements)
references
References 23 publications
23
253
1
4
Order By: Relevance
“…Aqueous extracts of betel quids and arecanuts that are generally used to make paan produced carcinomas of the cheek pouch and fore-stomach of rodents after subcutaneous or intragastric administration (IARC, 1985). Chewing is common among women in South-East Asia and the South Pacific Islands (IARC, 1985) where cervical cancer rates are very high (Parkin et al, 1997), and, in Southern India, paan chewing has been found to account for 87% of oral cancer in women (Balaram et al, 2002). In addition to paan chewing, low education, occupation in farming, low weight and low intake of vegetables and fruit were risk factors for cervical cancer in our study.…”
Section: Discussionsupporting
confidence: 47%
“…Aqueous extracts of betel quids and arecanuts that are generally used to make paan produced carcinomas of the cheek pouch and fore-stomach of rodents after subcutaneous or intragastric administration (IARC, 1985). Chewing is common among women in South-East Asia and the South Pacific Islands (IARC, 1985) where cervical cancer rates are very high (Parkin et al, 1997), and, in Southern India, paan chewing has been found to account for 87% of oral cancer in women (Balaram et al, 2002). In addition to paan chewing, low education, occupation in farming, low weight and low intake of vegetables and fruit were risk factors for cervical cancer in our study.…”
Section: Discussionsupporting
confidence: 47%
“…Similarly, the ethnic differences in risk in females in our study do not parallel differences in their alcohol consumption but are, to a certain extent, consistent with their higher prevalence of tobacco chewing, particularly among Bangladeshi women. This would accord with tobacco chewing being associated with higher risks of oral than pharyngeal cancers (Dikshit and Kanhere, 2000), the former effect being stronger in females (Balaram et al, 2002). A substantial limitation of the Health Survey is its not covering the use of betel alone, a well-established carcinogen (Chang et al, 2005); its use is common in some South Asian (and other) minority ethnic groups (Bedi and Gilthorpe, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Smoking tobacco can also be chewed alone or added to betel quid. The evidence that smokeless tobacco causes oral cancer was confirmed recently by the International Agency for Research on Cancer (IARC, 2004); and the risk is dependent on dose and duration of use of smokeless tobacco (Balaram et al, 2002).…”
Section: 1 Tobacco and Alcoholmentioning
confidence: 91%